The Radiation of the light excited layer of the alcohol solution of the dye Rhodamine 6G - Wardosanidze, Zurab V. (European Journal of Applied Sciences, 2021)
Was investigated experimentally the spectral and spatial characteristics of the radiation of a light-excited layer of an alcohol solution of the laser dye Rhodamine 6G (R6G) of rectangular and round geometric shape. The investigated layer is a part of the dye solution that is in direct contact with the bottom of the optical cells, the rectangular and circular sections of which determine geometric shape of the layer. Excitation of the layer was performed perpendicular to this layer by the second harmonic of the Nd+: YAG laser (λ = 532 nm) from the side of the cell bottom. Sufficiently strong, spectrally narrow-band radiation with a circular uniform distribution of intensity around the cells, in the plane of the luminescent layer, with a small divergence in the perpendicular plane was observed. It turned out that within the concentrations of the dye in the solution from 0.12w% to 0.03w%, the following processes are observed: Planely directed uniform, in intensity, radiation around the cell in the plane of the luminescent layer with a small vertical divergence; An increase in the amplitude of radiation pulses with a decrease in the concentration of the dye in the solution from 0.12w% to 0.03w%; Shifting of the maximum of the emission spectrum to the short-wave region and significant narrowing of the radiation spectrum and decrease of the vertical divergence of radiation.